Literatur Review: Penggunaan Terapi Non-farmakologi dalam Mengatasi Keluhan Nyeri di Unit Gawat Darurat - Sanjana, I Wayan; Agustini, Ni Luh Putu Inca Buntari; Wahyunadi, Ni Made Dewi; Maha Putra, I Nyoman Arya; Megayanti, Sri Dewi; Widyandari, Ni Made Ayu Sukma; Damayanti, Ida Ayu Manik (STIKES Adi Husada, 2024)
Pain management in the Emergency Department (ED) is crucial for humanitarian reasons and is associated with significant morbidity. Previously, pharmacologic therapies like acetaminophen, opioids, and NSAIDs were used, but they carry risks of side effects. Non-pharmacological interventions are often used in conjunction with pharmaceutical therapies to improve pain management and reduce opioid use. This study's purpose was to describe the non-pharmacological interventions that nurses can provide in addressing pain experienced by patients in the ED. This is a literature study from several databases such as Science Direct, ProQuest, SpringerLink, and PubMed using keywords combined with Boolean. The study's selection process involved searching 769 articles using keywords, excluding 27 duplicates and 712 articles not meeting research objectives. After a full-text review of 30 selected articles, 19 were excluded, and 11 were selected for inclusion. Acupuncture therapy is the most commonly used non-pharmacological therapy, followed by warm/cold compresses, distraction, and deep breath relaxation. Non-pharmacological therapies can be given to manage pain in patients in the ED. Combining pharmacological and non-pharmacological therapies can provide more analgesia for severe pain.